Relationship emotional intelligence and personality traits with organizational commitment among Iranian nurses - Zahra Taherinejad; Seyed Ahmad Ahmadi; Rozita Amani; Mahdieh Sadat Khoshouei (Gonabad University of Medical Sciences, 2017)
In the past three decades, organizational commitment has been of interest to researchers as one of the organizational attitudes. The aim of this study was to investigate the relationship of emotional intelligence and personality traits with organizational commitment among Iranian nurses. A total of 280 nurses were selected by multistage random sampling. Study tools included emotional intelligence inventory, Neo personality inventory and organizational commitment inventory. Results showed the positive and significant relationship of emotional intelligence and its dimensions (self-expression, self-regard, independence, social responsibility, problem solving, stress tolerance, impulse control, and optimism) with organizational commitment. Also, organizational commitment showed a positive and significant relationship with extroversion and conscientiousness. Moreover, components of self-expression, problem solving and stress tolerance in emotional intelligence are able to predict organizational commitment. Thus, these results indicate the importance of emotional intelligence and personality traits in organizational commitment.